2004
DOI: 10.1029/2003jd004030
|View full text |Cite
|
Sign up to set email alerts
|

Combined lidar‐radar remote sensing: Initial results from CRYSTAL‐FACE

Abstract: [1] In the near future, NASA plans to fly satellites carrying a two-wavelength polarization lidar and a 94-GHz cloud profiling radar in formation to provide complete global profiling of cloud and aerosol properties. The Cirrus Regional Study of Tropical Anvils and Cirrus Layers-Florida Area Cirrus Experiment (CRYSTAL-FACE) field campaign, conducted during July 2002, provided the first high-altitude collocated measurements from lidar and cloud profiling radar to simulate these spaceborne sensors. The lidar and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 28 publications
5
55
0
Order By: Relevance
“…Commonly observed differences between lidar-and radar-derived cloudiness that have been previously reported are seen in Fig. 2 (Comstock et al, 2002;McGill et al, 2004). When CloudSat (the radar) and CALIOP (the lidar) both detect clouds (6-15 • S), the lidar observes higher cloud tops than the radar.…”
Section: An Illustrative Cloudy Snapshotsupporting
confidence: 56%
See 1 more Smart Citation
“…Commonly observed differences between lidar-and radar-derived cloudiness that have been previously reported are seen in Fig. 2 (Comstock et al, 2002;McGill et al, 2004). When CloudSat (the radar) and CALIOP (the lidar) both detect clouds (6-15 • S), the lidar observes higher cloud tops than the radar.…”
Section: An Illustrative Cloudy Snapshotsupporting
confidence: 56%
“…Kahn et al, 2005), (2) reduce the effects of certain types of sampling biases, including those introduced by the attenuation of surface-based lidar and cloud radar in thick and precipitating clouds (Comstock et al, 2002;McGill et al, 2004), (3) provide a larger and statistically robust set of observations for comparison, and (4) facilitate near-global sampling for most types of clouds.…”
Section: Introductionmentioning
confidence: 99%
“…The 94 GHz (3.2 mm wavelength) cloud radar system (CRS; Li et al, 2004) and 9.6 GHz (3.1 cm wavelength) ER-2 Doppler radar (EDOP; Heymsfield et al, 1996) measure the radar reflectivity factor and mean Doppler velocity with a vertical gate spacing of 37.5 m. The 94 GHz radar reflectivity factor is calibrated against the 9.6 GHz radar near the cloud top (McGill, 2004), and the mean Doppler velocity measurements are calibrated using the surface signal (Li et al, 2004). The path-integrated attenuation (PIA) of the 94 GHz radar is estimated over the ocean using the surface reference technique (L'Ecuyer and .…”
Section: Measurements Used In the Retrievalmentioning
confidence: 99%
“…Lidar measurements are used to observe the clouds missed by the CRS since lidar is more sensitive to small ice particles and optically thin cirrus than radar. McGill et al [35] found that the τ missed by the CRS, but detected by the CPL, is in the range of 0.15-0.45. The CPL is a backscatter lidar with three wavelengths of 0.355, 0.532, and 1.064 µm [36].…”
Section: During Tcmentioning
confidence: 99%
“…The CPL measurements are used to compensate for the optically thin cirrus part missed by the CRS measurements [35]. Figure 7 shows the vertical structure of the cloud system as seen from the CRS and CPL measurements and the 15-m resolution τ profiles constructed from the CRS and CPL data for the pure ice layer.…”
Section: Optical Thickness Profiles From Combined Crs and Cpl Measurementioning
confidence: 99%